Student attitudes towards enterprise education in Poland: a positive impact - Paul Jones (Education + Training, 2008)
This paper aims to appraise the delivery of an enterprise education course to a cohort of Polish students evaluating its impact in encouraging entrepreneurial activity. The Polish economy continues its expansion with adoption of free market economies post communism. To encourage this growth, entrepreneurial activity must be encouraged within the next generation of entrepreneurs namely the student community. The course entitled Starting a New Enterprise (SANE) was developed to provide entrepreneurial skills and knowledge of the business planning process. The enterprise education literature questions its effectiveness in encouraging entrepreneurial activity. This study profiles the SANE course focusing on students entrepreneurial motivations, prior experiences and future intent.This study presents a quantitative review of the Polish students' reflections on the experience of enterprise within the SANE course. The basis for this investigation involved two semi‐structured questionnaires undertaken prior to and on completion of the course. In total, 59 students completed the first questionnaire and 50 respondents the second. The study found that Polish students had limited prior entrepreneurial experiences and expectations and welcomed the opportunity to undertake enterprise education. The findings suggested an equal proportion of male and female students aged 18‐24 favoured a future entrepreneurial career. Moreover, a quarter of all respondents welcomed an immediate entrepreneurial career on graduation and found value in the development of a business proposal. The findings suggested that entrepreneurial education informs entrepreneurial intent and career aspirations.